ANALISIS PARTISIPASI MASYARAKAT DAN KEPEMIMPINAN TERHADAP TINGKAT KEBERHASILAN PROYEK PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERDESAAN DI KECAMATAN GEROKGAK, BULELENG-BALI - Riska Wulandari, Putu; Bendesa, I K G; Nyoman Saskara, Ida Ayu (Buletin Studi Ekonomi; VOL.19.NO.2.AGUSTUS 2014.(PP 119-211), 2016)
The Effect of  Leadership on Public Participation, Public Participation to Influence Project Success Rate, and The Effect of Leadership on Project Success Rate of PNPM Mandiri Perdesaan in Gerokgak. The purpose of this study to determine the effect of leadership on public participation, public participation to influence project success rate, and the effect of leadership on project success rate of PNPM Mandiri Perdesaan in Gerokgak .In this case used data by questionnaire which distributed to 180 people who received the PNPM Mandiri Perdesaan program, divided into strata of the poor, middle and upper Data were analyzed with confirmatory methods, while the data analysis technique used is the analysis of the Structural Equation Model ( SEM ). Analysis showed that leadership has a positive effect on public participation, public participation slight positive effect on the project success rate, and leadership has a positive influence on the success rate of projects in PNPM Mandiri Perdesaan in Gerokgak.   Keywords: public participation, leadership, project success rate, PNPM Mandiri Perdesaan
Keywords: public participation, leadership, project success rate, PNPM Mandiri Perdesaan